Evaluating Marginal Policy Changes and the Average Effect of Treatment for Individuals at the Margin - Carneiro, Pedro; Heckman, James J.; Vytlacil, Edward (Econometrica, 2010)
This paper develops methods for evaluating marginal policy changes. We characterize how the effects of marginal policy changes depend on the direction of the policy change, and show that marginal policy effects are fundamentally easier to identify and to estimate than conventional treatment parameters. We develop the connection between marginal policy effects and the average effect of treatment for persons on the margin of indifference between participation in treatment and nonparticipation, and use this connection to analyze both parameters. We apply our analysis to estimate the effect of marginal changes in tuition on the return to going to college.